Maternal overweight impacts infant feeding patterns—the STEPS Study - Mäkelä, J; Vaarno, J; Kaljonen, A; Niinikoski, H; Lagström, H (European journal of clinical nutrition, 2014)
Objectives: We examined how maternal overweight impacts full breastfeeding (BF), total duration of BF and the age of introduction of complementary foods (CFs) and whether these have effect on children’s growth from 0 to 2 years. Subjects/Methods: From 1797 families participating in the STEPS Study, 848 children had data on BF and anthropometric data at 13 months and 2 years of age and were included in this study. Data on BF and CFs were collected using a self-administered follow-up diary. Information regarding maternal weight, height, pregnancy and delivery were received from maternity clinics and the National Longitudinal Census Files. The children’s weight and length/height were recorded during the study visits at 13 months and 2 years. Results: Overweight women breastfed fully (2.2 vs 2.8 months, P <0.0001) and totally (7.4 vs 9.0 months, P <0.0001) for a shorter time and introduced CFs earlier (4.1 vs 4.3 months, P =0.02) than normal weight women. Children of overweight women were heavier and had a higher body mass index at 2 years than children of normal weight women. At 2 years of age 30% of boys and 17% of girls were overweight or obese. However, children’s obesity risk was not increased by maternal overweight (odds ratio (OR) 1.04, P =0.12). Longer duration of full BF (OR 0.86, P =0.04) and partial BF (OR 0.91, P =0.02) and delayed introduction of CFs (OR 0.69, P =0.03) were protective against obesity. Conclusions: Our study suggests that women who were overweight or obese before pregnancy breastfed for a shorter time and introduced CFs earlier than normal weight women, which may further impact children’s growth.